The Simple Math of Writing Well Writing for the 21st Century - Harrop, Jennie A.; Open Textbook Library (Open Textbook Library, 2018)
Writing guides abound, but The Simple Math of Writing Well is one of a kind. Readers will find its practical approach affirming, encouraging, and informative, and its focus on the basics of linguistic structure releases 21st-century writers to embrace the variety of mediums that define our internet-connected world. As Harrop reminds us in the opening chapters of her book, we write more today than ever before in history: texts, emails, letters, blogs, reports, social media posts, proposals, etc. The Simple Math of Writing Well is the first guide that directly addresses the importance of writing well in the Google age.
Introduction: Myths And Rule Changes 1 -- Part I. The Sentence Equation -- 1. Main Verbs -- 2. Main Subjects -- 3. Terminal Punctuation Marks -- 4. Mid-Sentence Punctuation Marks -- 5. Eight Parts Of Speech -- 6. Consistency -- Part II. The Paragraph Equation -- 7. Topic Sentences -- 8. Evidence -- 9. Summary Sentences -- Part III. The Essay Equation -- 10. Thesis Statements -- 11. Introductions -- 12. Body Paragraphs -- 13. Conclusions -- Part IV. The Process Of Writing Well -- 14. Purpose -- 15. Audience -- 16. Voice -- 17. Context -- 18. Claims And Appeals -- 19. Clarity And Cohesion -- 20. Revision And Creativity -- Part V. Research -- 21. Finding Credible Evidence -- 22. Including Outside Evidence -- Part VI. Academic Formatting -- 23. Apa -- 24. Mla -- 25. Turabian -- Part VII. Beyond Academia -- 26. Emails -- 27. Letters -- 28. Reports And Proposals -- ConclusionAbout The Author
In English.
Description based on print resource
Keywords: Humanities -- Textbooks; Rhetoric -- Textbooks